Earthen Architecture in Muslim Cultures, Historical and Anthropological Perspectives. - Stéphane Pradines (Editor) (Arts and Archaeology of the Islamic World, 2018)
This edited volume follows the panel "Earth in Islamic Architecture" organised for the World Congress for Middle Eastern Studies (WOCMES) in Ankara, on the 19th of August 2014. Earthen architecture is well-known among archaeologists and anthropologists whose work extends from Central Asia to Spain, including Africa. However, little collective attention has been paid to earthen architecture within Muslim cultures. This book endeavours to share knowledge and methods of different disciplines such as history, anthropology, archaeology and architecture. Its objective is to establish a link between historical and archaeological studies given that Muslim cultures cannot be dissociated from social history. Contributors: Marinella Arena; Mounia Chekhab-Abudaya; Christian Darles; François-Xavier Fauvelle; Elizabeth Golden; Moritz Kinzel; Rolando Melo da Rosa; Atri Hatef Naiemi; Bertrand Poissonnier; Stéphane Pradines; Paola Raffa and Paul D. Wordsworth.